Sistem Pakar Untuk Mendeteksi Minat Dan Bakat : Sebuah Systematic Literature Review - Hafiz Firdaus; Agung Susilo Yuda Irawan (Department of Science and Technology Ibrahimy University, 2022)
We present a systematic literature review of an expert system to detect children's interests and talents. The purpose of this review is to plot all aspects of knowledge in the field of education, especially those using the expert system method, what children do in learning and how expert system methods can help in determining children's interests and talents. We conducted a systematic literature review of published studies that focused on the use of expert systems methods. The systematic review in this study is used to analyze how expert system methods can contribute massively to developments in the field of education. This research can also be used as a guideline for the most widely used expert system method to determine children's interests and talents. Research on determining children's talents and interests from 20 papers in a systematic literature review provides a broad understanding of the research conducted on what makes the system able to determine the best talents and interests for children through data obtained from experts